Penggunaan Kitab Durus Al-Lughah Al-‘Arabiyah Jilid 1 Untuk Pembelajaran Bahasa Arab di SDS IT Risalatul Haq Cicadas Purwakarta - Priyana, Tsara Dwi; Lailazhizah, Cahyainda; Munir, Dede Rizal (Madani: Jurnal Ilmiah Multidisiplin, 2025)
This research aims to analyze the use of the book Duruss Al-Lughah Al-'Arabiyyah in SDS IT Risalatul Haq Cicadas. This research is descriptive research with a qualitative approach. Data collected through observation, interviews and teaching practice. The subjects in this research were grade 3 students. Arabic language learning in this research emphasized the use of books in teaching and learning.The research results show that the direct method can be used as an effective learning method when learning Arabic. The advantage of direct media is that it makes it easier for students to understand and memorize the Arabic vocabulary conveyed by the teacher. Lack of students do not know the meaning of Arabic vocabulary